Prenatal Whole Genome Sequencing: Just Because We Can, Should We? - Donley, Greer (2012)
With whole genome sequencing set to become the preferred method of prenatal screening, we need to pay more attention to the massive amount of information it will deliver to parents—and the fact that we don't yet understand what most of it means.